2017
DOI: 10.21037/apm.2016.12.03
|View full text |Cite
|
Sign up to set email alerts
|

Patient versus health care provider perspectives on spirituality and spiritual care: the potential to miss the moment

Abstract: Several discrepancies in perception of spirituality, spiritual distress and spiritual care may hinder the ability of HCP's to effectively offer meaningful spiritual care. A focus on active listening, being led by the patient, and by providing presence may help limit the risk of a disconnect, or a 'miss', in the provision of spiritual care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 0 publications
0
30
0
Order By: Relevance
“…In other studies, they mentioned barriers as lack of time, lack of privacy and inadequate training (12,17). Also, several discrepancies in perception of spirituality, spiritual distress and spiritual care between patients and nurses may hinder the ability of healthcare professionals to effectively offer meaningful spiritual care (25). However, Wu showed that the spiritual needs of patients showed a significant relationship with the knowledge of nurses, suggesting that the perceived knowledge of the nurses generally corresponded with the spiritual care items that the patients required most (26).…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
“…In other studies, they mentioned barriers as lack of time, lack of privacy and inadequate training (12,17). Also, several discrepancies in perception of spirituality, spiritual distress and spiritual care between patients and nurses may hinder the ability of healthcare professionals to effectively offer meaningful spiritual care (25). However, Wu showed that the spiritual needs of patients showed a significant relationship with the knowledge of nurses, suggesting that the perceived knowledge of the nurses generally corresponded with the spiritual care items that the patients required most (26).…”
Section: Comparison With Other Studiesmentioning
confidence: 98%
“…The majority of studies were conducted in North America (n=26),19–44 with 11 from Europe,45–55 7 from Oceania4 56–61 and 6 from Asia 62–67. Participants were sampled from hospice settings (inpatient and hospice at home) in 27 studies,4 19 25 26 28–35 38–40 45–47 53 54 56–58 60–62 66 acute and long-term care settings in 9,22 27 44 55 59 63–65 67 general practices settings in 3,42 48 52 cancer centres in 4,23 24 36 37 a mix of settings in 3 studies21 49 50 and palliative care centres in 2 studies 43 51. One study provided no details on where participants were recruited from 41.…”
Section: Resultsmentioning
confidence: 99%
“…For 10 datasets, studies were included where they reported that the majority of patients (ie, ≥50%) had died within a year or before study completion 23 24 26 27 31 34 36 39 46 59 61. Twenty-one datasets included participants with a mix of chronic conditions,19 21 25 28–33 39–45 47–50 53 54 56–58 61 18 datasets included only participants with cancer,4 20 23 24 26 27 34–37 46 51 52 59 60 62–67 and 1 dataset included participants with only neurodegenerative diseases 55. Two datasets did not specify participants’ conditions 22 38…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations